2000
DOI: 10.1161/01.cir.102.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Hirudin Reduces Tissue Factor Expression and Attenuates Graft Arteriosclerosis in Rat Cardiac Allografts

Abstract: Background-Intravascular clotting has been implicated in the pathogenesis of cardiac allograft vasculopathy (CAV). We previously identified the expression of tissue factor (TF), the primary cellular initiator of blood coagulation, within the coronary intima, which was associated with neointimal thickening. In the present study, the effect of recombinant hirudin on CAV was assessed in Lewis to Fisher rat heterotopic cardiac allografts. Methods and Results-Transplant recipients were randomized to a control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…The histological specificity of vascular thrombin deposition is confirmed by hirudin, a specific thrombin inhibitor, blocking the staining with antithrombin antibody. Of note, it has been previously demonstrated that systemic hirudin administration to rat cardiac allograft recipients attenuates graft arteriosclerosis in close association with reduced tissue factor expression in transplant vasculature; tissue factor being necessary for thrombin formation (21). The current study extends these observations by showing that thrombin itself colocalizes with the microvasculature: a finding that is, to our knowledge, a unique observation in transplant biology.…”
Section: Discussionsupporting
confidence: 80%
“…The histological specificity of vascular thrombin deposition is confirmed by hirudin, a specific thrombin inhibitor, blocking the staining with antithrombin antibody. Of note, it has been previously demonstrated that systemic hirudin administration to rat cardiac allograft recipients attenuates graft arteriosclerosis in close association with reduced tissue factor expression in transplant vasculature; tissue factor being necessary for thrombin formation (21). The current study extends these observations by showing that thrombin itself colocalizes with the microvasculature: a finding that is, to our knowledge, a unique observation in transplant biology.…”
Section: Discussionsupporting
confidence: 80%
“…19 -21 Moreover, a potent thrombin inhibitor, hirudin, has been shown to attenuate experimental TA in rat cardiac allografts. 22 Our data now provide a mechanistic explanation for the link between TF and IH, through thrombin/PAR-1 signaling on circulating CD34 ϩ cells. PAR-1 is the archetypal member of a family of G-proteincoupled, 7 transmembrane-domain cell surface receptors, designated PAR-1 to PAR-4, [23][24][25][26] through which coagulation proteases mediate many of their proinflammatory effects.…”
Section: Discussionmentioning
confidence: 56%
“…estrogen, in cigarette smokers and in hyperhomocysteinemia [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] .…”
Section: Inflammationmentioning
confidence: 99%